Light at the end of the tunnel? Femtosecond pulses excite short-wavelength lasers - Hooker, S (Optical Society of American (OSA), 1997)
Hooker explores current work in the XUV and soft x-ray spectral region aimed at achieving "table-top" short-wavelength lasers.